Bulgaria : Improving Quality and Sustainability of the Health System - World Bank (Washington, DC, 2013)
Bulgaria has undertaken several significant health sector reforms during the past decade, but a large unfinished policy agenda remains. Compared to other EU countries, the share of out-of-pocket spending is significantly higher in Bulgaria, while government spending on health is relatively low. Various indicators of reported public satisfaction with the health system in Bulgaria are frequently the lowest in the EU. The hospital sector has seen rapid growth in recent years, putting the sustainability of the system in doubt and crowding out expenditures on more pressing priorities such as primary health care and the reimbursement of cost-effective drugs. Contrary to the imperative of improving health system efficiency, in recent years the Bulgarian hospital sector has grown in number of facilities, total number of hospitalizations, and the budget share dedicated to inpatient services. Each of these indicators is out of line with European standards. The primary health care system is well established but does not live up to its potential to provide efficient, high-quality care. Spending on primary health care is low, referral rates to higher levels of care are excessive, and the payment method does not provide adequate incentives for improved service provision. New by-laws on pharmaceutical policy and a new positive drug list mark a step forward, but important risks remain. The new drug list includes many new and expensive drugs, but the previous practice of using waiting lists to ration drug access in response to fixed budgets is no longer being implemented. As a result the new drug list poses a threat to the NHIF drug budget in 2009 which was originally programmed to be flat. The future direction of the national health insurance system needs to be clarified with reference to the key lessons emerging from the broad international experience with insurance system reform. In the short-term, protect health spending to mitigate the impact on the poor; and stabilize the drug budget during the final months of 2009, for example by considering a re-introduction of waiting lists for certain high-cost drugs and ensuring that adequate funds are available for nationally procured drugs. In the medium-term, initiate hospital sector restructuring in line with the master plan; and consider changing the financial incentives for hospitals, for example by enabling the NHIF to selectively contract with hospitals and to determine their budgets on the basis of case mix and projected service volume using the more accurate diagnosis-related groups (DRGs) instead of the current Clinical Care Pathways(CCPs); Focus on measures to improve the quality of services provided by strengthening the instruments of licensing and accreditation, for example through the establishment of an independent entity responsible for these functions; creating a link between hospital payment and information about the quality of their services; and reviewing the Clinical Care Pathways in light of up to date, international evidence on cost effective treatment protocols.